2016
DOI: 10.3174/ajnr.a5003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pial Collaterals on Infarct Growth Rate in Experimental Acute Ischemic Stroke

Abstract: Background and Purpose This work sought to mathematically model infarct growth and determine if infarct volume growth can be predicted by angiographic assessment of pial collateral recruitment in an experimental Middle Cerebral Artery Occlusion (MCAO) animal model. Materials and Methods Pial collateral recruitment was quantified using DSA, acquired 15 minutes following permanent MCAO in six canines based on a scoring system (Pc) and arterial arrival time (AAT). MRI based infarct volumes were measured 1,1.5,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 16 publications
3
46
0
Order By: Relevance
“…The extent of collateral-mediated reperfusion has a major impact on preserving the penumbra and often dictates stroke outcome (9)(10)(11)(12)(13). Several studies have demonstrated that the outcome after thrombolysis and thrombectomy therapy is highly dependent on patient collateral scoring (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of collateral-mediated reperfusion has a major impact on preserving the penumbra and often dictates stroke outcome (9)(10)(11)(12)(13). Several studies have demonstrated that the outcome after thrombolysis and thrombectomy therapy is highly dependent on patient collateral scoring (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…On day 1, qCBF images were acquired simultaneously with microsphere injection during normocapnia (target PaCO 2 range 30‐40 mmHg using room air) and during hypercapnia (target PaCO 2 range >60 mmHg induced by carbogen gas inhalation (5% CO 2 /95% O 2 )). On day 2 of the study, 4 of the 5 animals underwent permanent endovascular MCAO at the M1 segment while in a normocapnic state. One animal was not imaged on day 2 due to an unanticipated vessel perforation during MCAO, following which the animal was euthanized.…”
Section: Methodsmentioning
confidence: 99%
“…After completion of the MRI scans, the sheath was removed, and hemostasis was achieved. On day 2, the animal was brought back to the angiography suite where the right MCA was accessed endovascularly using fluoroscopic guidance as previously described . MCAO was verified by selective ipsilateral and contralateral internal carotid and vertebral arteriography (OEC9800, General Electric Healthcare, Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%
“…They do not take into account the extent of the penumbra that is influenced by other parameters such as collateral status and patient age. 68 Penumbra-based patient selection represents the logical next step in individualized stroke management and may result in better clinical outcomes. 69 Two methods exist of estimating the penumbra: clinical and radiological.…”
Section: Assessing Ischemia: Perfusionmentioning
confidence: 99%